Environmental pollution, biodiversity, and sustainable development : issues and remediation - Nangyal, Hasnain, 1987-; Khan, Muhammad Saleem, 1985- (Oakville, ON, Canada ; Palm Bay, Florida, USA : Apple Academic Press, 2020)
"Environmental Pollution, Biodiversity, and Sustainable Development: Issues and Remediation provides an extensive summary of biodiversity. It is the result of the assistance of environmentalists, researchers, policy experts, and academicians from across the globe sharing their research and knowledge on biodiversity and ways to mitigate the threat from climate change, over-utilization of natural resources, pollution, and more. The volume considers that biodiversity encompasses a wide range of biological processes, ranging from genetic diversity, species, populations, communities and ecosystems, landscapes and regions. This book, written by a panel of international experts in biodiversity, conservation biology, and evolution from different countries, including Iran, Pakistan, India, Bangladesh, Tajikistan, Russia, and others, highlights the human impact on biodiversity hotspots on a global scale. Topics include: the potential of phytoremediation, community-based conservation efforts, environmental pollution and the increasing risk of neurodegenerative diseases, ways to determine the most appropriate diversity indices, the volume provides an abundance of valuable research for faculty, students, and researchers in environmental sciences; government agencies, and many others."--
Phytoremediation Potential of Typha: An Approach to Biodiversity Conservation / H. Nangyal, N. Akhtar, M.M. Shahnaz, A. Nawaz, and M.S. Khan -- The Genetic Resources as an Inexhaustible Source of Biodiversity in Tajikistan / N. Firuza, H. Nangyal, A. Nawaz, and M. S. Khan -- Phytodiversity and Conservation Status of the Nara Desert, Pakistan / R. Qureshi -- The Simplest Way to Determine the Most Appropriate Diversity Indices in a Study Area / J. Parchizadeh -- Diversity of Pollen Grain Fertility and Crossing of Potato in Tajikistan / K. Partoev, K. Melikov, A. Naimov, H. Nangyal, and F.A. Khan -- Impact of Arsenic on Structural and Functional Composition of Dominant Bacterial Populations Associated with Various Natural Ecosystems / Soma Ghosh, Meenakshi Mukherjee, and Pinaki Sar -- Sea Buckthorn: Its Sustainable Utilization for Biodiversity Conservation / N. Malik, S. Saxena, H. Nangyal, T. Zohra, and H. Ikram -- Environmental Pollution: Increasing Risk of Neurodegenerative Diseases / H. Ikram and H. Nangyal -- Community-Based Conservation of the Sambhar Salt Lake, Jaipur, India / S. Kulshreshtha, G.V. Reddy, and H. Nangyal -- Biodiversity and Conservation of the Orphans of Rio in Northern Africa-Egypt: A Case Study / A.M. Abdel-Azeem and F.M. Salem -- Diversity of Functional Potential of Selected Medicinal Plants / Hasnain Nangyal, Ali Akbar, Imran Ali, Tanzeel Zohra, Uzma Sitara, and Muhammad Anwar -- Fungal Biodiversity of Foods and Feeds / Fatima Abdul Majeed and Ali Akbar -- Biodiversity and Distribution of Algae in Egypt / Heba S. Abbas -- Role of Diverse Medicinal Algae in a Therapeutic World / Heba S. Abbas.
OCLC-licensed vendor bibliographic record.
Keywords: Biodiversity; SCIENCE / Environmental Science; TECHNOLOGY / Environmental Engineering & Technology